Interdisciplinary collaboration: addressing global challenges through innovative learning strategies - Restu Adi Nugraha; Dasim Budimansyah; Yadi Ruyadi; Encep Syarif Nurdin; Mufid Hidayat (Inovasi Kurikulum, 2024)
In this era of globalization, students in Indonesia face increasingly complex challenges in  understanding, addressing, and contributing to global issues. However, the existing curriculum must often provide adequate perspectives and skills to tackle these global problems. Therefore, this research aims to provide students with a holistic, practical, and relevant learning experience to address global challenges through a Team-Based Project strategy that integrates compulsory courses in higher education with a global citizenship education approach. Cross-curricular collaboration helps students see the interconnectedness of various disciplines, essential in addressing complex global issues. Survey results indicate a variation of views among student groups regarding their understanding of global issues. This innovative learning strategy utilizes principles of behaviorist theory, such as stimulus-response, positive reinforcement, and social interaction, to create an engaging, relevant, and responsive learning environment tailored to students' needs. Through involvement in joint projects focused on global issues, students are stimulated to contribute and take concrete actions in seeking solutions and bringing about positive change on a larger scale. Thus, this learning strategy is expected to enhance students' understanding, skills, and commitment to addressing global challenges in the contemporary era.    Abstrak Dalam era globalisasi ini, mahasiswa di Indonesia dihadapkan pada tantangan yang semakin kompleks dalam memahami, menghadapi, dan berkontribusi terhadap isu-isu global. Namun, mata kuliah yang ada seringkali tidak mampu memberikan perspektif dan keterampilan yang memadai dalam mengatasi masalah global. Oleh karena itu, penelitian ini bertujuan untuk membuat mahasiswa untuk memberikan pengalaman belajar yang holistik, praktis, dan relevan dalam menghadapi tantangan global dengan strategi pembelajaran Team-Based Project yang menggabungkan mata kuliah wajib kurikulum di Perguruan Tinggi melalui pendekatan pendidikan kewarganegaraan global. Kolaborasi lintas mata kuliah membantu mahasiswa melihat keterkaitan antar disiplin ilmu, yang esensial dalam menghadapi masalah global yang kompleks. Hasil survei menunjukkan variasi pandangan dalam kelompok mahasiswa terkait pemahaman mereka tentang isu-isu global. Strategi pembelajaran inovatif ini memanfaatkan prinsip-prinsip teori behavioristik, seperti stimulus-respons, penguatan positif, dan interaksi sosial, untuk menciptakan lingkungan pembelajaran yang menarik, relevan, dan responsif terhadap kebutuhan mahasiswa. Melalui keterlibatan dalam proyek bersama yang berfokus pada isu-isu global, mahasiswa distimulus untuk memberikan kontribusi dan aksi nyata dalam mencari solusi dan membawa perubahan positif dalam skala yang lebih besar. Dengan demikian, strategi pembelajaran ini diharapkan dapat meningkatkan pemahaman, keterampilan, dan komitmen mahasiswa terhadap tantangan global di era kontemporer. Kata Kunci: mata kuliah wajib kurikulum; pembelajaran proyek; pendidikan kewarganegaraan global; strategi pembelajaran.